Industrial Trans Fatty Acids Stimulate SREBP2‐Mediated Cholesterogenesis and Promote Non‐Alcoholic Fatty Liver Disease - Oteng, Antwi‐Boasiako; Loregger, Anke; Weeghel, Michel; Zelcer, Noam; Kersten, Sander (Molecular nutrition & food research, 2019)
Scope The mechanisms underlying the deleterious effects of trans fatty acids on plasma cholesterol and non‐alcoholic fatty liver disease (NAFLD) are unclear. Here, the aim is to investigate the molecular mechanisms of action of industrial trans fatty acids. Methods and results Hepa1‐6 hepatoma cells were incubated with elaidate, oleate, or palmitate. C57Bl/6 mice were fed diets rich in trans‐unsaturated, cis‐unsaturated, or saturated fatty acids. Transcriptomics analysis of Hepa1‐6 cells shows that elaidate but not oleate or palmitate induces expression of genes involved in cholesterol biosynthesis. Induction of cholesterogenesis by elaidate is mediated by increased sterol regulatory element‐binding protein 2 (SREBP2) activity and is dependent on SREBP cleavage–activating protein (SCAP), yet independent of liver‐X receptor and ubiquitin regulatory X domain‐containing protein 8. Elaidate decreases intracellular free cholesterol levels and represses the anticholesterogenic effect of exogenous cholesterol. In mice, the trans‐unsaturated diet increases the ratio of liver to gonadal fat mass, steatosis, hepatic cholesterol levels, alanine aminotransferase activity, and fibrosis markers, suggesting enhanced NAFLD, compared to the cis‐unsaturated and saturated diets. Conclusion Elaidate induces cholesterogenesis in vitro by activating the SCAP–SREBP2 axis, likely by lowering intracellular free cholesterol and attenuating cholesterol‐dependent repression of SCAP. This pathway potentially underlies the increase in liver cholesterol and NAFLD by industrial trans fatty acids. The cholesterogenic effect of the trans fatty acid elaidate is due in part to its ability to reduce levels of intracellular cholesterol, and reduce the sensitivity of sterol regulatory element binding protein (SREBP) cleavage–activating protein (SCAP) to cholesterol. These properties result in the activation of the SREBP signaling pathway, leading to increased expression of genes involved in cholesterol biosynthesis.